Cognitive stimulation in older adults: an online intervention proposal during the pandemic. - Gomes Firmino, Rafael; Farias de Arruda, Leonardo; de Freitas Nunes, Victória Maria; do Carmo Eulálio, Maria (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2025)
It is known that cognitive decline occurs with human aging. Cognitive stimulation (CS) is understood as an essential tool for enhancing cognitive functions. This study aimed to evaluate the benefits of online CS and compare the performance of older adults after cognitive intervention sessions. Twenty older women were recruited through non-probability sampling and selected for convenience. The participants were divided into two groups: Experimental Group (EG) and Control Group (CG), with 10 members each. The cognitive interventions occurred in six weekly group sessions conducted online via the Google Meet platform. Data were analyzed using the R statistical software (R Core Team, 2019). Descriptive analysis was used for the means, and the t-test was applied for comparisons between the EG and CG. The results indicated that the EG showed significant improvements in cognition, particularly in the domains of attention and strategy adoption, as well as slight improvement in depressive symptoms after the CS sessions. Therefore, it is concluded that CS has significant effects on older adults.